Shape-stable sugarcane bagasse biochar/PEG-1000 composite phase change materials for thermal energy storage: enhanced thermal conductivity, leak resistance, and photothermal conversion - Qingyong Pang; Xiangqing Meng; Junfeng Han; WenJie Tan; Fukun Ma (Bioresource Technology, 2027)

Antifungal activity of major essential oils from Cinnamomum longepaniculatum against postharvest potato dry rot - Feng Han; Yingmei Ma; Lan Yun; Bingzhen Li; Junfeng Hao; Zhe Feng (Food and Humanity, 2026)

A stable shear-thinning XG-WAS@n-FeS slurry for simultaneous removal of Cr(VI) and TBBPA from water - Kaipian Shi; Junfeng An; Yu Yin; Li Yin; Ziyu Rong; Jinyu Han; Shiyin Li (Journal of Water Process Engineering, 2026)

Genomic characterization of the convergence of multidrug resistance and virulence in Salmonella Enteritidis from a broiler slaughterhouse in China - Xinfeng Han; Junfeng Peng; Junlin Li; Ruyi Kuang; Haotian Liu; Jing Xia; Min Cui; Yong Huang; Likou Zou (International Journal of Food Microbiology, 2026)

Mechanistic insights into enhanced permanganate activation by biochar derived from aluminum sludge: Critical roles of persistent free radicals and alumina - Zhongquan He; Yin Wei; Haonan Chen; Junyu Wu; Cheng Han; Xilei Jia; Junfeng Wang; Weiwei Hou; Chuanliang Zhao; Lanlan Liang; Liwei Yang (Environmental Research, 2026)

All-biomass-based beeswax/copper-loaded reed-derived porous carbon composite phase change materials for efficient solar photothermal conversion and thermal storage - Junfeng Han; Qing yong Pang; Qihang Li; Ke Yang; Liqiang Liu; Fukun Ma (Bioresource Technology, 2026)

From prediction to design: Optimized design of waste wood composites via GAN-augmented interpretable machine learning - Kongjie Gu; Junjie Xia; Shenjie Han; Xingying Zhang; Lu Li; Zhiqiang Dong; Liwen Zhou; Junfeng Hou (Bioresource Technology, 2026)

Triple-responsive supramolecular hydrogel with synergistic photothermal effect regulates inflammatory signaling to remodel the diabetic wound microenvironment and promote chronic wound healing - Jishang Sun; Jingwen Wang; Junfeng Ai; Ruxin Wang; Yanru Diao; Baoqin Han; Qingqing Bi; Jing Chang; Shuo Wang (Chemical Engineering Journal, 2026)

Waste cooking oil biodiesel alters combustion pathways to enhance volatile organic compound emissions and reduce intermediate/semi -volatile organic compounds in agricultural machinery - Fan Zhang; Bo Huang; Junfeng Cui; Yi Wang; Xinyi Wan; Lele Han; Gehui Wang; Yong Han; Yu Wang; Hai Guo; Min Cui (Journal of Hazardous Materials, 2026)

An AI-guided framework for discovery and evolution of sulfotransferases enables efficient sulfotyrosine bioproduction - Pan Zhang; Yan Chen; Zishuo Zeng; Ziyan He; Han Yu; Junfeng Shen; Ying Han; Huaxiang Deng; Xiaozhou Luo; Xinran Wang (Chemical Engineering Journal, 2026)

Bisphenol A promotes esophageal carcinogenesis by activating the MMP1–PCOLCE regulatory axis and remodeling the tumor immune microenvironment - Yawei Cui; Guohang Shen; Huiling Chen; Ruoyan Wang; Chengping Zhang; Lu Han; Kaiyong Wang; Yang Chen; Junfeng Li; Xia Gao; Yupei Dai (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

A new mechanism for magnetite formation in loess - Yifan Hua; Guiping Ren; Hua Li; Qijun Wang; John A. Tarduno; Junfeng Huang; Chengying Liu; Yiping Yang; Ronghua Wang; Xueqin Yang; Xiaohua Han; Yongxin Pan; et al. (Science Bulletin, 2026)

Metagenomic insights into the impacts of Vulcanococcus proliferation on microbial communities in a coastal bay - Fengyuan Zhang; Tianyue Zhou; Yumeng Feng; Yubin Chen; Qunfen Zhao; Qingxi Han; Junfeng Liu; Demin Zhang; Haibo Jiang; Huajun Zhang (Marine Environmental Research, 2026)

Uranium adsorption by extracellular polymeric substances from Desulfovibrio vulgaris UR1: Extraction optimization and binding mechanisms - Juncheng Han; Jing Zou; Guangming Xu; Xinyao Liu; Likun Jiang; Haotian Yang; Guangsheng Zhu; Jiaxin Bai; Yanqing Guo; Peng Wang; Ling Luan; Junfeng Dou (Journal of Hazardous Materials, 2026)

A parameterization for estimating ice sublimation in the Qilian mountains - Kaifeng Ma; Junfeng Liu; Chuntan Han; Rensheng Chen (Cold Regions Science and Technology, 2026)

In-situ oxidation of layered double hydroxides to form a Z-scheme heterojunction: Achieving high-efficiency phosphorus adsorption and synergistically promoting tetracycline photocatalytic decomposition - Qiang Zheng; Junfeng Li; Xiaoli Huang; Shiyu Han; Haoran Liu; Peicong Zhang; Yi Huang; Chengye Yang (Journal of Environmental Chemical Engineering, 2026)

Tuning the structural -OH on hydroxyapatite with fluorine significantly promoting the catalytic performance of CH4-CO2 reforming - Chao Li; Qiliang Gao; Meng Zhang; Jiahao Wang; Faen Song; Junfeng Zhang; Qingde Zhang; Yizhuo Han (Chemical Engineering Journal, 2026)

In-situ bioaugmentation of uranium-contaminated groundwater using Desulfovibrio vulgaris UR1: Mechanistic insights, laboratory validation, and field performance - Likun Jiang; Haotian Yang; Juncheng Han; Peng Wang; Xinyao Liu; Guangsheng Zhu; Ling Luan; Jiaxin Bai; Yanqing Guo; Junfeng Dou (Journal of Hazardous Materials, 2026)

Physical exercise mitigates the adverse effects of PM2.5 constituents on lung function: New evidence for inflammatory pathways from a crossover study - Pengpeng Wu; Qian Guo; Ling Qi; Yuchen Zhao; Mengyao Bian; Chen Wang; Bin Han; Junfeng (Jim) Zhang; Xiaoli Duan (Environmental Research, 2026)

Biochar-immobilized microorganisms drive removal and transformation of polycyclic aromatic hydrocarbons and their derivatives in soil: Efficiency and microbial succession dynamics - Shuying Geng; Fuqiang Fan; Zile Han; Suzhen Yin; Wei Cao; Guangming Xu; Aizhong Ding; Feiyong Chen; Shushuai Mao; Junfeng Dou (Bioresource Technology, 2026)

Optical diagnostic study on the combustion and soot formation process of nanobubble diesel - Han Wang; Liang Guo; Wanchen Sun; Yuying Yan; Hao Zhang; Miao Yang; Mengqi Jiang; Degang Li; Rong Xuan; Junfeng Zhang; Kaiqi Yang (Fuel, 2026)

A novel step-like deformation model for reservoir landslide monitoring with multi-temporal InSAR - Guoshi Liu; Qian Sun; Jun Hu; Leilei Liu; Wanji Zheng; Bing Han; Junfeng Li; Jihong Liu (Science China Earth Sciences, 2026)

Dynamics process of lead-zinc hydrolysis and characterization of its hydrolysis precipitates in a Pb-Zn-NaCl-H2O system at room temperature and pressure - Junfeng Liu; Yan Zhang; Runsheng Han; Pingtang Wei; Wei Zhu (Acta Geochimica, 2026)

Impact of temperature on the biogenic volatile organic compound (BVOC) emissions in China: A review - Yiming Yang; Fengbin Sun; Yusheng Chen; Shiyue Yang; Yuan Dai; Yiming Qin; Ning Zhang; Zhifeng Shu; Han Yan; Xinlei Ge; Junfeng Wang (Journal of Environmental Sciences, 2026)

Wide-targeted metabolomics elucidates metabolic compartmentalization and pathway enrichment in Leontopodium leontopodioides (Wild.) Beauv. Organs - Rule Yi; Gentu Ge; Junfeng Hao; Feng Han; Zhuna Bao; Yuqi Zou; Mingga Qi (Food Bioscience, 2026)

Biomass growth, nutrient removal, and microbial community dynamics in mono-, Co-, and sequential culture of screened cyanobacteria with microalgae for dairy wastewater treatment - Khin Khin Phyu; Suli Zhi; Junfeng Liang; Zengjun Yang; Run Zhao; Jiahua Liu; Yuang Cao; Han Wang; Keqiang Zhang (Bioresource Technology, 2026)

Influence of Grouting Pipe Lifting Rate on Vacuum Preloading Performance for Dredged Sludge - Zhou Changchen; Jin Fangyi; Xu Li; Li Dawei; Ni Junfeng; Yan Shuaixin; Xu Mintao; Han Song; Ge Bin; Wu Yehu; Zhang Ye (Geotechnical and Geological Engineering, 2026)

Rapidly evaluating electrochemical performance of transition metal disulfides for lithium ion batteries using machine learning classifier - Kun Han; Junfeng Li; Zhushun Zhang; Chenglong Wang; Jiabao Li; Yue Zhu; Zhijing Zhu; Xinjuan Liu; Guang Yang; Likun Pan (Chemical Engineering Journal, 2025)

Diagnostic potential of neutrophil extracellular traps in ulcerative colitis: a gene-based predictive model - Haijian Liang; Ying Xu; Xuan Zhang; Zhongyang Han; Junfeng Zhu (Molecular and Cellular Biochemistry, 2025)

Application of pre-stack geostatistical inversion in prediction of thin high-quality conglomerate reservoir in Shawan Depression, Junggar Basin - Zhiguo Cheng; Zeliang Liang; Junfeng Han; Tingting Hu; Gaoshan Deng; Chunming Jia; Jian Guan (Frontiers of Earth Science, 2025)

Morphodynamic changes of braided channels caused by increased runoff and sediment flux in the Yangtze river headwater on the Tibetan Plateau - Yujiao Liu; Yinjun Zhou; Xiongfei Wen; Zhongwu Jin; Zhijing Li; Xisheng Liu; Zhiwei Li; Junfeng Han (Journal of Hydrology, 2025)

Breaking bandwidth limit: All-medium metamaterial absorber engineered from heterostructure-anchored N-doped hollow carbon spheres - Jie Sui; Jiaxuan Zhang; Kemeng Yan; Jiayi Guo; Shuang Li; Jiaxin Liu; Jiangni Yun; Peng Kang; Yuhui Ren; Han Zhang; Lei Zhang; Ruiyong Chen; et al. (Chemical Engineering Journal, 2025)

Applicability of machine learning in modelling pan sublimation in cold regions - Kaifeng Ma; Junfeng Liu; Chuntan Han; Rensheng Chen (Theoretical and Applied Climatology, 2025)

Collaborative learning of multimodal fusion and audio-guided attention for fish feeding behavior analysis in aquafarm - Hao Wang; Miao Wang; Zhihan He; Aihui Han; Jinlong Long; Junfeng Wu; Hong Yu (Aquaculture International, 2025)

Energy burden and asthma prevalence in U.S. cities: An emerging social determinant of health - Soojin Han; Tina Hartert; Junfeng (Jim) Zhang; Wei-Chung Su; Pingsheng Wu; Youqin Huang; Qian Lu; Hongyu Wang; Hua Zhao; Yanfang Su; Ming Hu; Kai Zhang (Science of The Total Environment, 2025)

A strategy for the development of receptor-containing antibodies targeting malaria variant surface antigens - Yizhuo Wang; Hengfang Tang; Jiarui Li; Wanxue Wang; Ming Li; Chenchen Zhu; Han Dai; Hongxin Zhao; Lubin Jiang; Bo Wu; Junfeng Wang (Science China Life Sciences, 2025)

Acid-modified biochar drive U(VI) bioreduction via leachable persistent free radicals: Mechanisms of extracellular electron transfer and microbial synergy - Haotian Yang; Guangming Xu; Xinyao Liu; Juncheng Han; Likun Jiang; Kexin Shao; Guangsheng Zhu; Wei Cao; Junfeng Dou (Journal of Hazardous Materials, 2025)

Enclosed-terrain urbanized areas require vertically stratified air quality management: Insights from particulate matter vertical observations in China's Sichuan Basin - Xi Shu; Xue Qiao; Ya Tang; Philip K. Hopke; Qi Ying; Junfeng Wang; Bin Han; Zhongjun Xu; Zhonglin Xia; Yinhong Ma; Yuan Dai; Jun Leng (Journal of Environmental Management, 2025)

Global warming changes patterns of runoff and sediment flux in Tibetan Yangtze River headwater - Yinjun Zhou; Junfeng Han; Feng Wang; Xisheng Liu; Yujiao Liu; Xia Yan; Guoshuai Zhang; Junxiao Ma; Tong Wei; Zhongwu Jin; Zhijing Li; Dongfeng Li; et al. (Journal of Hydrology, 2025)

Field experiment and simulation for catalytic decomposition of ozone by exterior wall coatings with self-purifying materials - Lei Zhang; Jingwen Cui; Delai Wang; Yunfeng Li; Yafei Wang; Xue Han; Shuyang Xie; Junfeng Liu; Jinzhu Ma; Haixin Guo (Journal of Environmental Sciences, 2025)

PCBP2 in gastrointestinal cancers: fundamental mechanism and clinical potential - Chenyang Wang; Xi Chen; Lili Duan; Junfeng Chen; Liaoran Niu; Siyu Wei; Han Bai; Yujie Zhang; Wei Zhou; Jinqiang Liu; Wanli Yang; Yu Han; et al. (Journal of Molecular Medicine, 2025)

Converting static to Dynamic: Biomimetic Ultra-Sensitive Wide-Range flexible pressure sensor inspired by the Contact-Regulation process of scorpion pectines - Junqiu Zhang; Jiachao Wu; Lili Liu; Xiangbo Gu; Xueping Zhang; Xueyang Li; Zijian Shi; Yu Chen; Jiqi Gao; Junfeng Zhang; Tao Sun; Honglie Song; et al. (Chemical Engineering Journal, 2025)

Flos Puerariae-derived exosomes-like nanoparticles ameliorate alcoholic liver disease by targeting IL-11-related signaling pathways and reactive oxygen species - Siyue Li; Shuang Ma; Panpan Wang; Ying Xu; Jia Yu; Xuelin Qin; Yewen Zhang; Junfeng Wang; Wei Liu; Haoran Wang; Fei Han (Chemical Engineering Journal, 2025)

Insights into the enhanced uranium reduction efficiency through extracellular polymeric substances from Desulfovibrio vulgaris UR1 induced by mediating materials - Guangming Xu; Xinyao Liu; Juncheng Han; Kexin Shao; Haotian Yang; Jing Yuan; Junfeng Dou (Bioresource Technology, 2025)

Co-occurrence of mcr-9 and blaNDM-5 in Multidrug-Resistant Enterobacter hormaechei Strain Isolated from a Patient with Bloodstream Infection - Ru Li; Junfeng Wang; Weiting Zhang; Chenhao Zhao; Mingxiao Han; Hong Du; Haifang Zhang (Current Microbiology, 2025)

Carbonate composite materials for the leaching remediation of uranium-contaminated soils: Mechanistic insights and engineering applications - Juncheng Han; Guangming Xu; Xinyao Liu; Likun Jiang; Kexin Shao; Haotian Yang; Guangsheng Zhu; Aizhong Ding; Zhaorong Shang; Ling Chen; Junfeng Dou (Journal of Hazardous Materials, 2025)

Development and characterization of novel wood-based composite materials for solar-powered atmospheric water harvesting: A machine intelligence supported approach - Xingying Zhang; Yangyang Xu; Shenjie Han; Xiang Weng; Wenbo Che; Kongjie Gu; Ying Guan; Youming Yu; Derek Hao; Junfeng Hou (Journal of Cleaner Production, 2025)

A high-precision saltwater ice thickness and salinity detection method based on capacitive coupled planar microwave resonator - Han Shi; Mengjie Song; Junfeng Ge; Long Zhang; Xuan Zhang (Cold Regions Science and Technology, 2025)

Fish‐Finder: A robust small target detection method for aquaculture fish in low‐quality underwater images - Liang Liu; Junfeng Wu; Haiyan Zhao; Han Kong; Tao Zheng; Boyu Qu; Hong Yu (Journal of Fish Biology, 2025)
Underwater fish object detection serves as a pivotal research direction in marine biology, aquaculture management, and computer vision, yet it poses substantial challenges due to the complexity of underwater environments, occultations, and the small‐sized and frequently moving fish in aquaculture. Addressing these challenges, we propose a novel underwater fish object detection algorithm named Fish‐Finder. First, we engendered a structure titled “C2fBF,” utilizing the dual‐path routing attention protocol of BiFormer. The primary objective of this structure is to alleviate the perturbations induced by underwater intricacies during the phase of downsampling in the backbone network, thereby discerning and conserving finer contextual features. Subsequently, we co‐opted the RepGFPN method within our neck network—a distinctive approach that adeptly merges high‐level semantic constructs with low‐level spatial specifics, thus fortifying its multi‐scale detection prowess. Then, in an endeavor to diminish the sensitivity toward positional aberrations during the detection of diminutive aquatic creatures, we incorporated a novel bounding box regression loss function, the Wasserstein loss, to the existing CIoU. This innovative function gauges the congruity between the predicted bounding box Gaussian distribution and the reference bounding box Gaussian distribution. Finally, in regard to the dataset, we independently assembled a specific dataset termed “SmallFish.” This unique dataset, meticulously designed for the detection of small‐scale fish within intricate underwater settings, includes 5000 annotated images of small fish. Experimental results demonstrate that, compared to the state‐of‐the‐art detection methods, our proposed method improves the accuracy by and , and mean average precision (mAP) increases and in public dataset Kaggle‐Fish and our SmallFish dataset, respectively.

Associations of preconception air pollution exposure with growth trajectory in young children: A prospective cohort study - Jiawen Liao; Weili Yan; Yi Zhang; Kiros Berhane; Wu Chen; Zhenchun Yang; Chenyu Qiu; Yihui Ge; Zhipeng Bai; Bin Han; Jia Xu; Yong-hui Jiang; et al. (Environmental Research, 2025)

The nitrogen supply capacity and application methods of straw-chemical mixed fertilizer in the sweet corn variety ‘Zhetian 19’ - Junfeng Hou; Bin Chen; Ping Zhang; Yanli Wang; Heping Tan; Hailiang Han; Fei Bao; Fucheng Zhao (European Journal of Agronomy, 2025)

Microbial community assembly and co-occurrence patterns in Sanmen bay: A comparative analysis before and after nuclear power plant operation - Zhen Bao; Fengyuan Zhang; Qunfen Zhao; Qingxi Han; Junfeng Liu; Feng Xue; Demin Zhang; Dandi Hou; Huajun Zhang (Science of The Total Environment, 2025)

Pilot scale application of 226Ra-contaminated soil leaching remediation - Juncheng Han; Guangming Xu; Kexin Shao; Haotian Yang; Aizhong Ding; Zhaorong Shang; Hongtu Sun; Ling Chen; Zhiyuan He; Qiao Li; Hongbo Fan; Junfeng Dou (Chemosphere, 2024)

Microalgae create a highway for carbon sequestration in livestock wastewater: Carbon sequestration capacity, sequestration mechanisms, influencing factors, and prospects - Han Wang; Jiahua Liu; Khinkhin Phyu; Yu'ang Cao; Xiaoyu Xu; Junfeng Liang; Chein-Chi Chang; Keqiang Zhang; Suli Zhi (Science of The Total Environment, 2024)

Simultaneous algae-containing water treatment and power generation using floating iron-air electrocoagulation fuel cell - Xiaoyu Han; Jiangwei Lv; Yue Dong; Xin Zhao; Youpeng Qu; Junfeng Liu; Jie Zhang; Yujie Feng (Journal of Water Process Engineering, 2024)

Electrochemical degradation of aromatic organophosphate esters: Mechanisms, toxicity changes, and ecological risk assessment - Shaoyu Tang; Zhujun Luo; Linbin Zhu; Yuanyuan Yu; Minghan Zhu; Hua Yin; Lanfang Han; Lei Xu; Junfeng Niu (Journal of Hazardous Materials, 2024)

Regulatory roles of extracellular polymeric substances in uranium reduction via extracellular electron transfer by Desulfovibrio vulgaris UR1 - Guangming Xu; Haotian Yang; Juncheng Han; Xinyao Liu; Kexin Shao; Xindai Li; Guanying Wang; Weifeng Yue; Junfeng Dou (Environmental Research, 2024)

Influence of scour depth and flow velocity field on large-diameter pier group pile foundations - Junfeng Shi; Changhai Han; Huijuan Guo; Kaiwen Yu; Kang Han (Frontiers in Marine Science, 2024)
Sea-crossing bridges face critical challenges due to scour, which can destabilize foundations. This study investigates the scour characteristics of the large-diameter main pier of the Haiwen Bridge, with a pile diameter of 4.3 meters. Seabed changes were monitored over 630 days using field tests and numerical simulations. The study analyzed the relationship between flow velocity and scour depth, revealing that the maximum recorded scour depth was 3.65 meters at the upstream side. A linear regression model, developed from 75 sets of field data, produced a formula to estimate maximum local scour depth. Validation against field measurements showed a strong correlation, with the calculated values deviating by less than 10% from observed data. The findings indicate that upstream scour pits were 1.5 times wider and deeper than those downstream, while a shallow triangular scour zone, extending 1.2 times the pile diameter, formed downstream. Recommendations for scour protection include hydrological considerations, particularly on the upstream side and areas lacking sediment sources.

Short-term air pollution and greenness exposures on oxidative stress in urban and peri-urban residents in Beijing: A part of AIRLESS study - Wenhao Qi; Hanbin Zhang; Yiqun Han; Wu Chen; Yanbo Teng; Lia Chatzidiakou; Benjamin Barratt; Rod Jones; Frank Kelly; Tong Zhu; Junfeng Zhang; John S. Ji; et al. (Science of The Total Environment, 2024)

Synergistic dielectric and magnetic effects boosting electromagnetic wave absorption in Flower-Ball-like VSe2@CoFe2O4 composites - Jinchang Liu; Leyao Xu; Cong Shao; Zhaolin Liu; Guowei Zhang; Yuang Guan; Yunyao Zhang; Xiaoyi Lei; Yang Dai; Wu Zhao; Junfeng Yan; Han Zhang (Chemical Engineering Journal, 2024)

Shear behavior of precast bridge deck panels with UHPC wet joints - Zhangdi Ren; Junfeng Jia; Jian Li; Menghan Hu; Bin Li; Qiang Han; Xiuli Du (Engineering Structures, 2024)

A novel dual functional gradient Zn(O,S)/Mg electron-selective contact for dopant‐free silicon solar cells with efficiencies approaching 21 % - Junfeng Zhao; Zhongqing Zhang; Shengpeng Xie; Fangfang Liu; Yongtai Zhen; Sen Li; Wenzhu Liu; Anjun Han; Liping Zhang; Zhengxin Liu; Yun Sun; Wei Liu (Chemical Engineering Journal, 2024)

Mixed microalgal culture enhances biofilm adhesion during treatment of livestock wastewater: The role of extracellular polymeric substances - Jiahua Liu; Zengjun Yang; Khinkhin Phyu; Yu’ang Cao; Han Wang; Xiaoyu Xu; Junfeng Liang; Keqiang Zhang; Chein-Chi Chang; Suli Zhi (Chemical Engineering Journal, 2024)

Analysis of the influence of interlayer discontinuity conditions on the dynamic responses of multilayered poroelastic soil - Han Zejun; Zhang Junfeng; Yang Linqing; Hou Zhenkun; Yuan Bingxiang (Computers and Geotechnics, 2024)

Sedimentation history linked to global change in the alpine Damqu Wetland of the Yangtze River headwater in interior Tibetan Plateau - Qinjing Shen; Xinqi Feng; Yinjun Zhou; Penghui Lin; Yuexin Liu; Yuansen Lai; Junfeng Han; YuJiao Liu; Yixuan Wang; Shuai Zhu; Zhijing Li; Zhongping Lai (Quaternary Geochronology, 2024)

Targeting GLUT1 degradation with assembling glycopeptide for cancer inhibition - Xia Wu; Jun Shen; Xingyue Jiang; Hong Han; Zenghui Li; Yatong Xiang; Dan Yuan; Junfeng Shi (Chemical Engineering Journal, 2024)

Reindeer (Rangifer tarandus) hindlimb joint kinetics: propulsive and energy storage mechanisms and mechanical work - Guoyu Li; Rui Zhang; Hao Pang; Junfeng Wang; Dan Jin; Xumin Sun; Dianlei Han; Zhisong Li; Lige Wen (Polar Biology, 2024)

Orbital global change drove fluvial aggradation and incision in Tibetan upper Mekong river: Chronological perspectives - Yinjun Zhou; Junfeng Han; Qinjing Shen; Yantian Xu; Yaling Tao; Penghui Lin; Yuansen Lai; Yixuan Wang; Zhongping Lai (Quaternary Geochronology, 2024)

Optimization of flavonoids extracted from hawthorn （Crataegus pinnatifida） by ultrasonic-assisted deep eutectic solvent - Xiaojing Sun; Meiling Fu; Shihao Lou; Dandan Li; Xue Han; Shan Gao; Jianhua Xiu; Junfeng Wang; Yuanyuan Ren (Food Bioscience, 2024)

Synthesis of ultrasmall vanadium ferricyanide nanocrystallines with the aidance of graphene self-assembled fibers towards reinforced zinc storage performance - Haolun Ma; Ruiyong Chen; Binbin Liu; Junfeng Yan; Gang Wang; Wu Zhao; Han Zhang; Luhui You (Chemical Engineering Journal, 2024)

Study on spray characteristics of micro-nano bubble premixed fuel - Rong Xuan; Liang Guo; Ningning Cai; Wanchen Sun; Yuying Yan; Hao Zhang; Yanling Chen; Han Wang; Junfeng Zhang; Youxin Ge (Fuel, 2024)

Microalgal-bacterial consortia for the treatment of livestock wastewater: Removal of pollutants, interaction mechanisms, influencing factors, and prospects for application - KhinKhin Phyu; Suli Zhi; Junfeng Liang; Chein-Chi Chang; Jiahua Liu; Yuang Cao; Han Wang; Keqiang Zhang (Environmental Pollution, 2024)

Biogeography and impact of nitrous oxide reducers in rivers across a broad environmental gradient on emission rates - Sibo Zhang; Xinghui Xia; Leilei Yu; Shaoda Liu; Xiaokang Li; Junfeng Wang; Yue Zheng; Lanfang Han; Qian Tan; Zhifeng Yang (Environmental Microbiology, 2024)
Microbial communities that reduce nitrous oxide (N 2 O) are divided into two clades, nosZ I and nosZ II. These clades significantly differ in their ecological niches and their implications for N 2 O emissions in terrestrial environments. However, our understanding of N 2 O reducers in aquatic systems is currently limited. This study investigated the relative abundance and diversity of nosZ I‐ and nosZ II‐type N 2 O reducers in rivers and their impact on N 2 O emissions. Our findings revealed that stream sediments possess a high capacity for N 2 O reduction, surpassing N 2 O production under high N 2 O/NO 3 ‐ ratio conditions. This study, along with others in freshwater systems, demonstrated that nosZ I marginally dominates more often in rivers. While microbes containing either nosZ I and nosZ II were crucial in reducing N 2 O emissions, the net contribution of nosZ II‐containing microbes was more significant. This can be attributed to the nir gene co‐occurring more frequently with the nosZ I gene than with the nosZ II gene. The diversity within each clade also played a role, with nosZ II species being more likely to function as N 2 O sinks in streams with higher N 2 O concentrations. Overall, our findings provide a foundation for a better understanding of the biogeography of stream N 2 O reducers and their effects on N 2 O emissions.

Study on the remediation of uranium-contaminated soils by compound leaching: Screening of leaching agents and a pilot-scale application - Juncheng Han; Jing Zou; Xindai Li; Aizhong Ding; Zhaorong Shang; Hongtu Sun; Ling Chen; Zhiyuan He; Qiao Li; Hongbo Fan; Junfeng Dou (Journal of Cleaner Production, 2024)

Bibliometric insights into the evolution of uranium contamination reduction research topics: Focus on microbial reduction of uranium - Guangming Xu; Xindai Li; Xinyao Liu; Juncheng Han; Kexin Shao; Haotian Yang; Fuqiang Fan; Xiaodong Zhang; Junfeng Dou (Science of The Total Environment, 2024)

Recent advances in electrospinning-nanofiber materials used in advanced oxidation processes for pollutant degradation - Heshan Zheng; Han Lu; Shuo Li; Junfeng Niu; Yoong Kit Leong; Wen Zhang; Duu-Jong Lee; Jo-Shu Chang (Environmental Pollution, 2024)

Seismic response of an irregular slope containing surficial weak layer and internal fractures in Dadu River, southwest China - Jianxian He; Yunsheng Wang; Jianjun Zhao; Yingbin Zhang; Junfeng Wu; Jiangtao Wei; Liming Han (Landslides, 2024)

The challenge of monitoring snow surface sublimation in winter could be resolved with structure-from-motion photogrammetry - Junfeng Liu; Rensheng Chen; Shaoxiu Ma; Chuntan Han; Yongjian Ding; Shuhai Guo; Xueliang Wang (Journal of Hydrology, 2024)

Green tea polyphenols alleviate β-conglycinin-induced anaphylaxis by modulating gut microbiota in rats - Yang Zhou; Shugui Zheng; Shuo Yang; Jiguang Li; Kai Yang; Junfeng Han; Shuang Duan (Food Bioscience, 2023)

Evaluation of 12 precipitation products and comparison of 8 multi-model averaging methods for estimating precipitation in the Qilian Mountains, Northwest China - Yong Yang; Rensheng Chen; Yongjian Ding; Wenwu Qing; Hongyuan Li; Chuntan Han; Zhangwen Liu; Junfeng Liu (Atmospheric Research, 2023)

Fish Recognition in the Underwater Environment Using an Improved ArcFace Loss for Precision Aquaculture - Liang Liu; Junfeng Wu; Tao Zheng; Haiyan Zhao; Han Kong; Boyu Qu; Hong Yu (Fishes, 2023)
Accurate fish individual recognition is one of the critical technologies for large-scale fishery farming when trying to achieve accurate, green farming and sustainable development. It is an essential link for aquaculture to move toward automation and intelligence. However, existing fish individual data collection methods cannot cope with the interference of light, blur, and pose in the natural underwater environment, which makes the captured fish individual images of poor quality. These low-quality images can cause significant interference with the training of recognition networks. In order to solve the above problems, this paper proposes an underwater fish individual recognition method (FishFace) that combines data quality assessment and loss weighting. First, we introduce the Gem pooing and quality evaluation module, which is based on EfficientNet. This module is an improved fish recognition network that can evaluate the quality of fish images well, and it does not need additional labels; second, we propose a new loss function, FishFace Loss, which will weigh the loss according to the quality of the image so that the model focuses more on recognizable fish images, and less on images that are difficult to recognize. Finally, we collect a dataset for fish individual recognition (WideFish), which contains and annotates 5000 images of 300 fish. The experimental results show that, compared with the state-of-the-art individual recognition methods, Rank1 accuracy is improved by 2.60% and 3.12% on the public dataset DlouFish and the proposed WideFish dataset, respectively.

Gastrointestinal digestion and absorption of soybean β-conglycinin in an early weaned piglet model: An initial step to the induction of soybean allergy - Shugui Zheng; Shuangyang Yin; Guixin Qin; Jiaqi Yao; Simiao Liu; Junfeng Han; Yang Zhou; Shuang Duan (Food Chemistry, 2023)

Mussels-inspired design a multi-level micro/nano re-entrant structure amphiphobic PVDF membrane with robust anti-fouling for direct contact membrane distillation - Bang Li; Tengfei Tian; Xia Zhang; Changrui Han; Yanbin Yun; Xinfeng Zhu; Junfeng Wu (Desalination, 2023)

Identification of critical effect factors for prediction of spatial and intra-annual variability of shallow groundwater nitrate in agricultural areas - Chunying Wang; Xinliang Wang; Gengchen Zhang; Feifei Zhang; Junfeng Li; Shuai Chen; Sabine Sauvage; José-Miguel Sánchez-Pérez; Yuping Han; Junguo Liu (Science of The Total Environment, 2023)

Cytotoxic pyridine alkaloids from a marine-derived fungus Arthrinium arundinis exhibiting apoptosis-inducing activities against small cell lung cancer - Yiwei Hu; Shuai Ma; Xiaoyan Pang; Mengjing Cong; Qianqian Liu; Fanghai Han; Junjian Wang; Weineng Feng; Yonghong Liu; Junfeng Wang (Phytochemistry, 2023)

Degradation of xylan by human gut Bacteroides xylanisolvens XB1A - Tingting Zhao; Han Yue; Junfeng Peng; Yingmin Nie; Longzhen Wu; Tingting Li; Wei Niu; Chuan Li; Zhengqing Zhang; Meixia Li; Kan Ding (Carbohydrate Polymers, 2023)

Marine fungus-derived alkaloid inhibits the growth and metastasis of gastric cancer via targeting mTORC1 signaling pathway - Shuai Ma; Yiwei Hu; Jianjiao Chen; Xiaojuan Wang; Chenxi Zhang; Qianqian Liu; Guodi Cai; Hong Wang; Jianwei Zheng; Qianqian Wang; Lin Zhong; Bin Yang; et al. (Chemico-Biological Interactions, 2023)

Promotional effect of Cs modification to NASICON material on aldol condensation of acetic acid and formaldehyde to acrylic acid - Kaiwen Zheng; Qiliang Gao; Chao Li; Guojie Zhang; Qingde Zhang; Junfeng Zhang; Yizhuo Han; Yisheng Tan (Fuel, 2023)

The electrical conductivity of granite: The role of hydrous accessory minerals and the structure water in major minerals - Kui Han; Xinzhuan Guo; Xuben Wang; Junfeng Zhang; Sinan Özaydin; Dewei Li; Simon Martin Clark (Tectonophysics, 2023)

Ni/Y2O3-ZrO2 catalysts for dry reforming of methane: Increased Y content boosted the performance via enhancing metal-support interaction and surface oxygen species - Meng Zhang; Xiaotian Zhou; Chao Li; Wenjing Yi; Qiliang Gao; Junfeng Zhang; Qingde Zhang; Yizhuo Han (Fuel, 2023)

A new strategy to strongly release sweet-enhancing volatiles from goji pomace using trivalent iron salts - Xue Han; Na Zhang; Lingxi Luo; Yanyan Zhang; Mengze Wang; Xiaoyu Yin; Bo Zhang; Junfeng Fan (Food Research International, 2023)

CRISPR/Cas9-based point-of-care lateral flow biosensor with improved performance for rapid and robust detection of Mycoplasma pneumonia - Rong Zhu; Han Jiang; Chaoyou Li; Yan Li; Min Peng; Junfeng Wang; Qian Wu; Chao Yan; Qingli Bo; Jie Wang; Chenlin Shen; Panzhu Qin (Analytica Chimica Acta, 2023)

Exploring the relationship between deep roots and shoot growth of wheat under different soil moisture: A large soil column experiment 1 - Dan Liu; Siwei Mou; Yufeng Zou; Baoping Yang; Ruixia Ding; Junfeng Nie; Xudong Zhang; Zhikuan Jia; Qingfang Han (Rhizosphere, 2023)

The interfacial destabilization of bile salt-emulsified oil droplets, essential for lipase function, is mediated by Lycium barbarum L. leaf polysaccharides - Na Zhang; Xue Han; Rumeng Yu; Xiaomin Tang; Bo Zhang; Yanyan Zhang; Xiaoyu Yin; Wenrui Ni; Mengze Wang; Bolin Zhang; Junfeng Fan (Food Hydrocolloids, 2023)

Effects of coal molecular structure and pore morphology on methane adsorption and accumulation mechanism - Jingshuo Zhang; Xiaoming Ni; Ying Han; Junfeng Lin (Frontiers of Earth Science, 2023)

Optical bulk-boundary dichotomy in a quantum spin Hall insulator - Junfeng Han; Pengcheng Mao; Hailong Chen; Jia-Xin Yin; Maoyuan Wang; Dongyun Chen; Yongkai Li; Jingchuan Zheng; Xu Zhang; Dashuai Ma; Qiong Ma; Zhi-Ming Yu; et al. (Science Bulletin, 2023)

Growth, health status and gut microbiota of the scalloped spiny lobster (Panulirus homarus) at different salinities - Hu Chen; Junfeng Pan; Yongzhen Wang; Yanbing Qiao; Fenglu Han; Chang Xu; Ardavan Farhadi; Erchao Li (Aquaculture, 2023)

Sensitive biosensors based on topological insulator Bi2Se3 and peptide - Yujiu Jiang; Peng Zhu; Jinge Zhao; Shanshan Li; Yetong Wu; Xiaolu Xiong; Xu Zhang; Yuxiang Liu; Jiangyue Bai; Zihang Wang; Shiqi Xu; Minxuan Wang; et al. (Analytica Chimica Acta, 2023)

Productivity of Leymus chinensis grassland is co-limited by water and nitrogen and resilient to climate change - Yujie Shi; Yunna Ao; Baixin Sun; Johannes M. H. Knops; Jinwei Zhang; Zhihan Guo; Xianming De; Jiayu Han; Yuheng Yang; Xiaoyu Jiang; Chunsheng Mu; Junfeng Wang (Plant and Soil, 2022)

Transcriptomic and metabolomic reprogramming in cotton after Apolygus lucorum feeding implicated in enhancing recruitment of the parasitoid Peristenus spretus - Xinzheng Huang; Junfeng Kou; Weixia Jing; Xiaoqiang Han; Danfeng Liu; Somayyeh Ghasemzadeh; Peiyao Sun; Wangpeng Shi; Yongjun Zhang (Journal of Pest Science, 2022)

Fast grain-boundary ionic conduction in multiphase aggregates as revealed by electrical conductivity measurements - Kui Han; Xinzhuan Guo; Junfeng Zhang; Xuben Wang; Simon M. Clark (Contributions to Mineralogy and Petrology, 2021)

Responses of soil N 2 O emissions and their abiotic and biotic drivers to altered rainfall regimes and co‐occurring wet N deposition in a semi‐arid grassland - Yujie Shi; Junfeng Wang; Yunna Ao; Jiayu Han; Zhihan Guo; Xinyuan Liu; Jinwei Zhang; Chunsheng Mu; Xavier Le Roux (Global Change Biology, 2021)
Global change factors such as changed rainfall regimes and nitrogen (N) deposition contribute to increases in the emission of the greenhouse gas nitrous oxide (N 2 O) from the soil. In previous research, N deposition has often been simulated by using a single or a series of N addition events over the course of a year, but wet N deposition actually co‐occurs with rainfall. How soil N 2 O emissions respond to altered rainfall amount and frequency, wet N deposition, and their interactions is still not fully understood. We designed a three‐factor, fully factorial experiment with factors of rainfall amounts (ambient, −30%) rainfall frequency (ambient, ±50%) and wet N deposition (with/without) co‐occurring with rainfall in semi‐arid grassland mesocosms, and measured N 2 O emissions and their possible biotic and abiotic drivers. Across all treatments, reduced rainfall amount and N deposition increased soil N 2 O emissions by 35% and 28%, respectively. A significant interactive effect was observed between rainfall amount and N deposition, and to a lesser extent between rainfall frequency and N deposition. Without N deposition, reduced rainfall amount and altered rainfall frequency indirectly affected soil N 2 O emissions by changing the abundance of nirK and soil net N mineralization, and the changes in nirK abundance were indirectly driven by soil N availability rather than directly by soil moisture. With N deposition, both the abundance of nirK and the level of soil water‐filled pore space contributed to changes in N 2 O emissions in response to altered rainfall regimes, and the changes in the abundance of nirK were indirectly driven by plant N uptake and nitrifier (ammonia‐oxidizing bacteria) abundance. Our results imply that unlike wetter grassland ecosystems, reduced precipitation may increase N 2 O emissions, and N deposition may only slightly increase N 2 O emissions in arid and semi‐arid N‐limited ecosystems that are dominated by grasses with high soil N uptake capacity.

The prevalence and risks of major comorbidities among inpatients with pulmonary tuberculosis in China from a gender and age perspective: a large-scale multicenter observational study - Wanli Kang; Jian Du; Song Yang; Jiajia Yu; Hongyan Chen; Jianxiong Liu; Jinshan Ma; Mingwu Li; Jingmin Qin; Wei Shu; Peilan Zong; Yi Zhang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Frozen ground change and its potential influence on river discharge in the Tienshan Mountains, northwestern China - Xiqiang Wang; Rensheng Chen; Chuntan Han; Yong Yang; Junfeng Liu; Zhangwen Liu; Shuhai Guo; Yaoxuan Song (Hydrological Sciences Journal, 2021)

Response of shallow soil temperature to climate change on the Qinghai–Tibetan Plateau - Xiqiang Wang; Rensheng Chen; Chuntan Han; Yong Yang; Junfeng Liu; Zhangwen Liu; Shuhai Guo; Yaoxuan Song (International Journal of Climatology, 2021)
Under climate change, soil temperature change remarkably influences regional landscapes, ecosystems, hydrological processes, and other parameters. Based on daily soil temperature data from 56 stations from 1965 to 2014, the spatiotemporal variations in shallow soil temperature (0, 5, 10, 15, and 20 cm) on the Qinghai–Tibetan Plateau (QTP) were investigated. The mean shallow soil temperature decreased obviously with altitude both annually and seasonally, except in winter. Primarily dependent on station latitude, the spatial distribution of winter soil temperature was significantly affected by the snow cover conditions. As the soil depth increased, the soil temperature showed a cooling trend in spring and summer but a warming trend in autumn and winter. In the past 50 years, the shallow soil temperature increased considerably on the QTP both annually and seasonally. The warming rate of soil temperature was greatly dependent on station altitude in winter and dependent on latitude in summer and longitude in autumn. Unlike the increasing air temperature that was contributed mainly by winter, the warming rate of soil temperature in winter at depths of 5, 10, 15, and 20 cm was obviously lower than that in other seasons and air temperature in winter. This occurrence may be caused by relatively less snow cover in winter, which produces a weak insulation effect and further makes the soils more vulnerable to cooling from cold air. For the entire region, the soil temperature variability was strongly correlated with the change in air temperature but weakly correlated with precipitation. Although the warming rate in shallow soil tended to be low (high) at stations with a high amount of precipitation (snow cover), the influence of precipitation (including snow) on shallow soil temperature was limited on the QTP in the past few decades.

Soil temperature change and its regional differences under different vegetation regions across China - Xiqiang Wang; Rensheng Chen; Chuntan Han; Yong Yang; Junfeng Liu; Zhangwen Liu; Shuhai Guo; Yaoxuan Song (International Journal of Climatology, 2021)
Changes in soil temperature will exert an important influence on the management and utilization of vegetation and agricultural production, whereas the spatiotemporal variations in soil temperature under different vegetation regions across China remain largely unknown. The shallow soil temperatures (0–20 cm) during the growing season (May–September) from 1965 to 2014 across China were analysed, and the findings showed that the spatial distribution of shallow soil temperature was determined primarily by latitude in eastern China (east of 110°E), and by altitude in western China (west of 110°E) with some high (low) temperature centres. The vegetation regions with relatively low soil temperatures are mainly concentrated in high altitude and high latitude areas, which have relatively large differences in soil temperature at different depths and relatively high soil warming rates. Over the past 50 years, shallow soil temperatures increased greatly during the growing season at the site, vegetation region and nation scales, but the warming rate and its relationship with climate change varied greatly. The soil temperature variables were affected substantially by air temperature and precipitation in the subtropical forest and tropical forest regions but were affected primarily by air temperature in the other vegetation regions. This difference may be due to the spatial difference in precipitation amounts across China, which affected the soil temperature via soil moisture feedback. Further study indicated that the warming rate in shallow soil was higher in stations (vegetation regions) with less precipitation than in those with more precipitation.

Construction and immune protection evaluation of recombinant virus expressing Newcastle disease virus F protein by the largest intergenic region of fowlpox virus NX10 - Yan Zhao; Zongxi Han; Xiaocai Zhang; Xuemei Zhang; Junfeng Sun; Deying Ma; Shengwang Liu (Virus Genes, 2020)

Creative conservation in China: releasing captive giant pandas into the wild - Mingsheng Hong; Wei Wei; Hong Zhou; Junfeng Tang; Han Han; Zejun Zhang (Environmental Science and Pollution Research, 2019)

Overall survival time prediction for high-grade glioma patients based on large-scale brain functional networks - Luyan Liu; Han Zhang; Jinsong Wu; Zhengda Yu; Xiaobo Chen; Islem Rekik; Qian Wang; Junfeng Lu; Dinggang Shen (Brain Imaging and Behavior, 2019)

Effects of snow-depth change on spring runoff in cryosphere areas of China - Xiaojiao Liu; Rensheng Chen; Junfeng Liu; Xiqiang Wang; Baogui Zhang; Chuntan Han; Guohua Liu; Shuhai Guo; Zhangwen Liu; Yaoxuan Song; Yong Yang; Qin Zheng; et al. (Hydrological Sciences Journal, 2019)

Construction of a dietary-cure Saccharomyces cerevisiae expressing long-acting glucagon-like peptide-1 and investigation of its hypoglycemic activity in type 2 diabetes mellitus mouse model - Pingzhe Jiang; Chao Ma; Junfeng Hao; Yike Han; Minggang Li (Journal of Biosciences, 2019)

Precipitation–altitude relationships on different timescales and at different precipitation magnitudes in the Qilian Mountains - Lei Wang; Rensheng Chen; Yaoxuan Song; Yong Yang; Junfeng Liu; Chuntan Han; Zhangwen Liu (Theoretical and Applied Climatology, 2018)

Evolution of intron-poor clades and expression patterns of the glycosyltransferase family 47 - Junfeng Tan; Zhenyan Miao; Chengzhi Ren; Ruxia Yuan; Yunjia Tang; Xiaorong Zhang; Zhaoxue Han; Chuang Ma (Planta, 2018)

Characterizing Physiological and Proteomic Analysis of the Action of H2S to Mitigate Drought Stress in Young Seedling of Wheat - Huina Ding; Qiaoxia Han; Dongyun Ma; Junfeng Hou; Xin Huang; Chenyang Wang; Yingxin Xie; Guozhang Kang; Tiancai Guo (Plant Molecular Biology Reporter, 2018)

Lolium Perenne as the Cultivation Plant in Hydroponic Ditch and Constructed Wetland to Improve Wastewater Treatment Efficiency in a Cold Region - Yongxiang Ren; Yang Liu; Junfeng Sun; Hao Lu; Lei Yang; Cancan Chen; Yun Han (Wetlands, 2016)

Study on the mesoscale eddies around the Ryukyu Islands - Shuzong Han; Changsan Xu; Huiming Wu; Gang Wang; Junfeng Pei; Yongbin Fan; Xingchi Wang (Acta Oceanologica Sinica, 2016)

Effect of initial biomass density on growth and astaxanthin production of Haematococcus pluvialis in an outdoor photobioreactor - Junfeng Wang; Danxiang Han; Milton R. Sommerfeld; Congming Lu; Qiang Hu (Journal of Applied Phycology, 2013)

Early subduction–exhumation and late channel flow of the Greater Himalayan Sequence: implications from the Yadong section in the eastern Himalaya - Junfeng Gong; Jianqing Ji; Baofu Han; Jianjun Chen; Dongxia Sun; Baolong Li; Jing Zhou; Jiyao Tu; Dalai Zhong (International Geology Review, 2012)

Effects of anthropogenic activities on chemical contamination within the Grand Canal, China - Xiaolong Wang; Jingyi Han; Ligang Xu; Junfeng Gao; Qi Zhang (Environmental Monitoring and Assessment, 2011)

The Spen Homolog Msx2-Interacting Nuclear Target Protein Interacts with the E2 Ubiquitin-Conjugating Enzyme UbcH8 - Junfeng Li; Jishu Wang; Xi Yang; Junlin Li; Hongyan Qin; Xiao Dong; Yangting Zhu; Liang Liang; Yingmin Liang; Hua Han (Molecular and Cellular Biochemistry, 2006)